THE IMPACT OF MENSTRUATION ON SCHOOL ATTENDANCE IN SOUTH AFRICA - THANDI S NGOMANE; MOKOKO P SEBOLA (Social Sciences and Education Research Review)
This article analysis the impact of menstruation on girl's school attendance and how that impact on women's participation in developmental issues. It is estimated that most girl-children miss attending classes when they are on a menstruating cycle. Since menstruation only affect girls, boys do not have disrupted school attendance as compared to girls. Absence from school due to menstruation is argued to happen mostly at primary school than at high school level. The onset of menstruation can be very traumatic for young girls if unprepared. This can also be exacerbated by patriarchal views of menstruation as dirty and something that must be hidden from the public eye, including to men. In South Africa the debate around access to sanitary products by schoolgirls resulted in the removal of Value Added Tax (VAT) from sanitary towels. This article is qualitative in approach and uses desktop study method. The perception of menstruation is largely viewed from a patriarchal perspective, resulting in shame for girl child. The study concludes that missing school due to menstruation has a serious effect on girl's performance at school and in turn women's future participation in development since it has direct impact on women's literacy levels.